The Bonhoeffer reader - Green, Clifford J.; Dejonge, Michael P.; Lofgren, Alisha (Fortress Press, 2013)
For the first time in nearly 20 years, the essential theological writings of Dietrich Bonhoeffer have been drawn together in a helpful and concise one-volume format. The Bonhoeffer Reader brings the best English translation to readers, students, and scholars and provides a ready-made introduction to the thought of this essential thinker.